Regulator of Calcineurin 1 in Periodontal Disease. (15th June 2016) - Peters, Ulrike; Solominidou, Eleni; Korkmaz, Yüksel; Rüttermann, Stefan; Klocke, Astrid; Flemmig, Thomas Frank; Beikler, Thomas
Abstract : Nuclear factor of activated T-cells (NFAT) and NF-kB pathway associated processes are involved in the pathogenesis of various inflammatory disorders, for example, periodontal disease. The activation of these pathways is controlled by the regulator of calcineurin 1 (RCAN1). The aim of this study was to elucidate the role of RCAN1 in periodontal disease. Healthy and inflamed periodontal tissues were analyzed by immunohistochemistry and immunofluorescence using specific rabbit polyclonal anti-RCAN1 antibodies. For expression analysis human umbilical vein endothelial cells (HUVEC) were used. HUVEC were incubated for 2 h with Vascular Endothelial Growth Factor (VEGF) or with wild type and laboratory strains of Porphyromonas gingivalis ( P. gingivalis ). Expression analysis of rcan1 and cox2 was done by real time PCR using specific primers for rcan1.4 and cox2 . The expression of rcan1 was found to be significantly suppressed in endothelial cells of chronically inflamed periodontal tissues compared to healthy controls. Rcan1 and cox2 were significantly induced by VEGF and wild type and laboratory P. gingivalis strains. Interestingly, the magnitude of the rcan1 and cox2 induction was strain dependent. The results of this study indicate that RCAN1 is suppressed in endothelial cells of chronically inflamed periodontal tissues. During an acute infection, however, rcan1 seems to be upregulated in endothelial cells, indicating a modulating role in immune homeostasis of periodontal tissues.